A table in the presence : the dramatic account of how a U.S. Marine battalion experienced God's presence amidst the chaos of the war in Iraq /: the dramatic account of how a U.S. Marine battalion experienced God's presence amidst the chaos of the war in Iraq. (©2004) - Unknown
No abstract available